Uma análise de performances de personagem feminino por personagem masculino : o filme Tootsie em questão - Atallah, Mariana de Castro (2013)
This dissertation analyzed the four main performances practices of Michel Dorsey, the main character of Tootsie movie (played by Dustin Hofmann), in the light of the gender communication situation. The interest in this study arose when noticed that, to produce the movie, a scientific study was necessary. The justification of this work rests in the fact that the author, Lilian Glass, helped Dustin Hoffmann to perform as a woman. Then, we tried to subvert what Glass (1992) established, as we discussed the notion of gender, from the performative theory paradigm, based on the theory of Butler (2003) and Eckert e McConell-Ginet (2010). Therefore, we emphasized the deconstruction of the difference in the gender study paradigm, assuming a critic stance and positioning for the adoption of the performative theory in the gender study. We analyzed, however, the data production – Tootsie movie scenes – from the theory notion that the interactional sociolinguist is an instrumental to performance. We noticed, nevertheless, that the tootsie movie is not adherent to the essentialist consolidated values, but a source of questions to those. The satiric view is an integrant part of the group of these elements, it ridicule the social gender conception. The fact that the director asked the gender specialist Lilian Glass for help demonstrate the objective to show better interpretations of the stereotyped vision of being men or women. And from the co-constructions of these interpretations emanate the subtle meanings; the satiric comedy; the fact that being a man or a woman is not static. In other words, individual can possess multiple gender identities, depending of the contextual, historical and social situations, and from the performative practices.